ANALISA BIAYA KLAIM NASABAH TERHADAP LABA PERUSAHAAN ASURANSI (Studi Kasus Pada PT. Prudential Life Assurance ) - Widi Winarso (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
This studyaims to determinehow the developmentcost ofthe claim, firmsprofitandhow much influencethe cost ofclaims against thecompany'sprofitsPTPrudentialLife Assurancefrom 2008until 2012.The method usedinthis researchisdescriptivequantitativemethod. Objectscapturedpopulationisclaim costsand profitby usingthe samplefinancial statementsof PTPrudentialLifefrom 2008until 2012. The results ofnormality testcalculationofthe two variableshave asignificance valueof0.05. This showsthatthesetwo variablesare normally distributed. From thetestresults ofsimplelinearregression, variablecustomerkliam(x) has apositiveeffecton profitsof firms. Keyword : customer claims, corporate profits